Fearless leadership [ how to overcome behavioral blind spots and transform your organization - Malandro, Loretta A. (McGraw-Hill, 2009)
It takes true vision and courage to meet the challenges of a changing global market. But to align new strategies, overcome obstacles, and enact real change, it's necessary to change behavior on an individual level throughout an organization. This book offers a unified game plan of specific behavioral techniques proven to promote positive change